Cross-Cultural Delivery of e-Learning Programmes: Perspectives from Hong Kong - Wong, Andrew Lap-sang (International Review of Research in Open and Distributed Learning, 2007)
The growing popularity of e-learning may pose one of the greatest challenges currently facing traditional educational institutions. The questions often asked are how, rather than whether, to embrace this new form of instructional delivery and how to create an appropriate learning environment for the learners. Educational institutions in Hong Kong have the option of adopting programmes or learning materials developed in other parts of the world for local learners, or not. Such an approach of acquiring learning materials is not without risks in terms of the suitability of materials embedded with cultural contents ‘foreign’ to local learners, or in terms of the suitability of assumptions in the communication context. What are the issues involved in the globalization of education through e-learning? This paper explores – from a critical-dialectical perspective – the implications of globalization on educational policy through cross-border delivery of educational programmes by e-learning, with particular attention given to the threat of cultural imperialism. The paper concludes that Hong Kong seems to be coping with ‘cultural imperialism’ rather well because of its unique history of being a cross-road for East and West, and also with some recommendations to e-learning providers to mitigate the potential damage of cross-cultural delivery of e-learning.